2020
DOI: 10.3390/ani10112111
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Hypothalamic Alternative Splicing Events and Variants in Ovine Fecundity-Related Genes

Abstract: Previous studies revealed that alternative splicing (AS) events and gene variants played key roles in reproduction; however, their location and distribution in hypothalamic fecundity-related genes in sheep without the FecB mutation remain largely unknown. Therefore, in this study, we described the hypothalamic AS events and variants in differentially expressed genes (DEGs) in Small Tail Han sheep without the FecB mutation at polytocous sheep in the follicular phase vs. monotocous sheep in the follicular phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
2
4
0
Order By: Relevance
“…Combined transcriptomic and proteomic analyses have been widely used to study the mechanisms underlying the development of multiple traits in domestic animals. Our study has revealed a weak positive correlation between the transcriptome and proteome following β-CG induction, which is consistent with previous studies. These findings suggest post-transcriptional regulation of gene expression in β-CG-induced intestinal damage in piglets. In addition, six genes/proteins in the DEGs and DEPs overlapped, including VAT1L, PSAT1, SCD, VDR, PRND, and AHSP.…”
Section: Discussionsupporting
confidence: 92%
“…Combined transcriptomic and proteomic analyses have been widely used to study the mechanisms underlying the development of multiple traits in domestic animals. Our study has revealed a weak positive correlation between the transcriptome and proteome following β-CG induction, which is consistent with previous studies. These findings suggest post-transcriptional regulation of gene expression in β-CG-induced intestinal damage in piglets. In addition, six genes/proteins in the DEGs and DEPs overlapped, including VAT1L, PSAT1, SCD, VDR, PRND, and AHSP.…”
Section: Discussionsupporting
confidence: 92%
“…Melatonin secretion is closely related to oestrous in sheep, and the EEF2 gene induces melatonin secretion from the pituitary gland to participate in the oestrous of sheep [ 69 ]. Zhang et al found that the relative expression of the ASPA gene in the hypothalamus changed significantly during oestrous and was associated with litter size in sheep [ 70 ]. During domestication, several genes associated with the physical characteristics of sheep were artificially selected in a targeted manner.…”
Section: Discussionmentioning
confidence: 99%
“…All selected ewes were bred in Tianjin (117.2 E, 39.13 N) with full consideration of animal welfare. Experimental animals were treated with vaginal sponges (InterAg Co., Ltd., New Zealand) (progesterone 300 mg, placed twelve days), and the removal time was set as 0 h. Refer to previous research, six ewes (three polytocous sheep and three monotocous sheep) were euthanized at 48 h (follicular phase), and six ewes (three polytocous sheep and three monotocous sheep) at 216 h (luteal phase) [78,79]. After euthanasia, pituitary samples were collected and preserved as soon as possible for subsequent analysis.…”
Section: Ethical Consideration and Samples Collectionmentioning
confidence: 99%